Bats of Mount Silabur, Sarawak, and Its Potential for Conservation - Emy Ritta, Jinggong; Praveena, Rajasegaran; Muhd Amsyari, Morni; Julius Willian, Dee; Azroie, Denel; Faisal Ali, Anwarali Khan (UNIMAS Publisher, 2022)
Karst landscape is recognised as one of the biologically important areas especially for bats. The limestone caves and forest within the landscape provide essential resources for the local bat fauna, albeit bat populations are severely threatened by anthropogenic disturbances occurring within and surrounding the ecosystem. In Sarawak, studies on bat diversity are biased towards protected areas, leaving aside non-protected areas including private lands such as Mount Silabur. Surveys on bat diversity were conducted at the limestone outcrop and the surrounding matrix of Mount Silabur with the primary aim of developing the first checklist of bats at Mount Silabur. A total of 27 species were recorded from 12 sampling nights representing approximately 34% of the total bat species recorded in Sarawak. The Cox’s Roundleaf Bat (Hipposideros coxi), a rare Bornean endemic species, was recorded from the cave system, signifying an important record for the area and also Sarawak. Furthermore, this is the sixth locality record for the species in Sarawak, Borneo. Interestingly, the total number of bat species recorded from Mount Silabur represented about 72% of the total bat species recorded (27 out of 38 species) from other major touristic caves in western Sarawak; Fairy Cave Nature Reserve and Wind Cave Nature Reserve. This warrants a need to develop an action plan to protect and conserve Mount Silabur cave system and the surrounding forest for its potential to serve as a shelter for bats and other cave and forest dependent taxa. The local community should implement and adhere to guidelines for cave related activities to minimise human driven disturbances on the ecosystem and its inhabitants.